TRAINING OF JUDICIAL PRACTICE TO IMPROVE HANDLING SKILLS CIVIL CASES - Maria Yosepin Endah Listyowati; Dyah Erlina Sulistyaningrum; Lilik Prihatin; Suryadi; M. Achwan; Moch.Amin; Suyani; Diyah Setya (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
Trial training through moot court is expected to produce graduates who are not only superior in theory, but also skilled in actual legal practice. This is one of the strategic efforts to improve the quality of legal education in universities, especially for students in legal studies programs, including at PDKU Ponorogo UNMER Malang. It's just that sometimes this activity is not carried out comprehensively due to a lack of adequate preliminary training. Such training should include a basic understanding of procedural law necessary to carry out moot court practice well.This service in the form of training aims to provide insight and experience regarding the main components of civil procedural law as well as skills in compiling case lawsuit files. In this way, participants are expected to be able to understand and apply the basic principles of civil procedural law and be able to prepare lawsuit files correctly.The result of this training activity is that students experience increased knowledge in the basics of civil procedural law and gain a better understanding of the procedures and principles underlying judicial practice. The next result is an increase in ability to compile lawsuit files and become more skilled in collecting, organizing and presenting relevant information to prepare lawsuit documents that meet applicable legal standards.Overall, this moot court practice training provides significant benefits for students in understanding and applying civil procedural law and increasing their competency in the legal field. It is hoped that this can support the educational process and improve the quality of graduates of the PDKU Ponorogo UNMER Malang Legal Studies Program